ANALYSIS OF A DRAMA SCRIPT ENTITLED “AYAHKU PULANG” BY USMAR ISMAIL USING A SEMIOTIC APPROACH - Gunawan, Inra; Syarifudin, Syachrul; Syahrial, Ilham; Putra, Adita Widara (Media Inovasi Pendidikan dan Publikasi, 2024)
Language and literature are two interrelated components that cannot be separated from each other. Literature is an expression of human feelings expressed through experiences, thoughts, ideas, passion, and beliefs in the form of beautiful language. Meanwhile, language itself is a means of communication used by humans both in oral and written form. This research uses a descriptive qualitative approach with the object of study of a drama script entitled “AYAHKU PULANG” by Usmar Ismail. Meanwhile, the research subject as well as the primary data source are signs or symbols containing semiotics contained in the drama script. Meanwhile, secondary data sources or data collection techniques use text analysis techniques on the research subject. The results of this study show that there are quite a lot and diverse semiotic elements.